In the privy council [electronic resource] : in the matter of the complaint of the House of Assembly of Newfoundland against the Honorable H.J. Boulton, chief justice of Newfoundland; case of the chief justice. - Boulton, Henry John, 1790-1870.; Newfoundland. House of Assembly. ([S.l. : s.n., 1837)
Tables. "Frère, Foster & Co." Electronic reproduction. Mode of access: Internet. 44